Gga-miR-205a Affecting Myoblast Proliferation and Differentiation by Targeting CDH11 - Wang, Zhijun; Ouyang, Hongjia; Chen, Xiaolan; Yu, Jiao; Abdalla, Bahareldin A.; Chen, Biao; Nie, Qinghua (Frontiers in Genetics, 2018)
Non-coding RNAs especially miRNAs have found to play important roles during skeletal muscle development. Our previous RNA-Seq performed on breast muscle tissue from 7 weeks old Recessive White Rock and Xinhua Chicken and leg muscle tissue from female Xinghua Chicken at three development time point (11 embryo age, 16 embryo age, and 1day post hatch) (accession number GSE62971 and GSE89355, respectively) showed that miR-205a and CDH11 were differentially expressed genes. In this study, we found that miR-205a was sharply upregulated at 11 embryo age (E11) and reached another peak at E15 after a continuous decline. The overexpression of miR-205a could inhibit both Quail muscle clone 7 cell lines (QM7) and chicken primary myoblast (CPM) proliferation, at the meantime promote the differentiation of myoblasts by directly binding to the 3’UTR of CDH11. Conversely, Overexpression of CDH11 significantly facilitated QM7 and CPM proliferation and hampered CPM differentiation. The Dual-Luciferase Reporter Assay results showed that MyoG and HNF-1 could possibly regulate the expression of miR-205a by binding to the active region of miR-205a. Altogether our data suggest that MyoG could possibly stimulate miR-205a expression to suppress CDH11, which promotes myoblasts proliferation while represses the differentiation.